Biotechnological and Immunological Platforms Based on PGL-I Carbohydrate-Like Peptide of Mycobacterium leprae for Antibodies Detection Among Leprosy Clinical Forms - Lima, Mayara Ingrid Sousa; Capparelli, Fausto Emilio; Dias Oliveira, Jaqueline das Dores; Fujimura, Patrícia Tiemi; Moraes, Emilly Caroline dos Santos; Araujo, Ester Cristina Borges; Silva, Neide Maria; Alves-Balvedi, Renata Pereira; Brito-Madurro, Ana Graci; Goulart, Isabela Maria Bernardes; Goulart, Luiz Ricardo (Frontiers in Microbiology, 2020)
Phenolic glycolipid I (PGL-I) is an abundant antigen on the Mycobacterium leprae cell wall, commonly used for operational classification of leprosy patients. Our aim was to develop PGL-I mimotopes with similar characteristics and functions of the native antigen. We have used a random peptide phage display (PD) library for selections against the monoclonal antibody anti-PGL-I. After three selection cycles, six peptides were identified. All sequences were interspersed by a spacer generating a chimeric peptide (PGLI-M3) that was artificially synthesized. The highly reactive peptide was submitted to a reverse PD selection with a single-chain Fv (scFv) antibody fragment combinatorial library. The most reactive scFv was then validated by ELISA against both native PGL-I and two derived synthetic (NDO and ND-O-HSA). We have further proved the scFv specificity by detecting M. leprae bacilli in leprosy lesions through immunohistochemistry. We then described its applicability in ELISA for all clinical forms and household contacts (HC). Afterward, we showed differential binding affinities of PGLI-M3 to sera (anti-PGL-I IgM) from all leprosy clinical forms through Surface Plasmon Resonance (SPR). ELISA IgM detection showed 89.1% sensitivity and 100% specificity, considering all clinical forms. Positivity for anti-PGL-I IgM was two-fold higher in both HC and patients with paucibacillary forms in hyperendemic regions than in endemic ones. The SPR immunosensor was able to differentiate clinical forms with 100% accuracy. This is the first time that a PGL-I mimotope has efficiently mimicked the carbohydrate group of the M. leprae antigen with successful immunoassay applications and may become a substitute for the native antigen.